Riociguat: Clinical research and evolving role in therapy. Issue 7 (30th December 2020) - Klinger, James R.; Chakinala, Murali M.; Langleben, David; Rosenkranz, Stephan; Sitbon, Olivier
Abstract : Riociguat is a first‐in‐class soluble guanylate cyclase stimulator, approved for the treatment of adults with pulmonary arterial hypertension (PAH), inoperable chronic thromboembolic pulmonary hypertension (CTEPH), or persistent or recurrent CTEPH after pulmonary endarterectomy. Approval was based on the results of the phase III PATENT‐1 (PAH) and CHEST‐1 (CTEPH) studies, with significant improvements in the primary endpoint of 6‐minute walk distance vs placebo of +36 m and +46 m, respectively, as well as improvements in secondary endpoints such as pulmonary vascular resistance and World Health Organization functional class. Riociguat acts as a stimulator of cyclic guanosine monophosphate synthesis rather than as an inhibitor of cGMP metabolism. As with other approved therapies for PAH, riociguat has antifibrotic, antiproliferative and anti‐inflammatory effects, in addition to vasodilatory properties. This has led to further clinical studies in patients who do not achieve a satisfactory clinical response with phosphodiesterase type‐5 inhibitors. Riociguat has also been evaluated in patients with World Health Organization group 2 and 3 pulmonary hypertension, and other conditions including diffuse cutaneous systemic sclerosis, Raynaud's phenomenon and cystic fibrosis. This review evaluates the results of the original clinical trials of riociguat for the treatment of PAH and CTEPH, and summarises the body of work that has examined the safety and efficacy of riociguat for the treatment of other types of pulmonary hypertension.